Intergranular corrosion evaluation of friction stir welded AISI 410S ferritic stainless steel - Caetano, Gerbson de Queiroz (2019)
This study aimed to investigate the susceptibility of AISI 410S ferritic stainless steel to intergranular corrosion when friction stir welded (FSW) using the double-loop electrochemical potentiokinetic reactivation (DL-EPR) test. The highest values obtained for the ratio between the reactivation current (Ir) and the activation current (Ia) were found at the top of the advancing side for the two conditions tested. The steel for Condition 1, which was welded with a rotational speed of 800 rpm and high heat input, gave Ir/Ia peaks 60% greater than Condition 2, which was welded with a rotational speed of 450 rpm and a lower heat input. These peaks were attributed to the presence of precipitates with high chromium content of about 21%. In these FSW welds the sensitization of the AISI 410S steel was detected by the electrochemical test according to the intensity of the undesirable phases formed. The DL-EPR test was clearly able to quantify the different levels of sensitization in the FSW welds according to the energy used by the process parameters.